2011
DOI: 10.1002/0471140864.ps2702s64
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Programmable Protein Arrays: Versatile Tools for Array‐Based Functional Protein Studies

Abstract: Protein microarrays offer a global perspective on the function of expressed gene products. However, technical issues related to the stability and dynamic range of microarrays printed with purified protein have hampered their widespread adoption. Taking an alternate approach, the Nucleic Acid Programmable Protein Array (NAPPA) is constructed by spotting protein-encoding plasmid DNA at high density, in addressable fashion, on an array surface. Proteins are subsequently generated in situ just prior to experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…We have widely published detailed protocols for producing NAPPA arrays, as well as published on recent improvements in the method 21,3537 . In addition, we have published a video tutorial for how to build NAPPA arrays (https://www.youtube.com/watch?v=Ur1fg9jQv04) 36 . Furthermore, researchers who do not have direct access to resources to build, print, screen, scan, or analyze their own arrays can make use of our central plasmid repository (https://dnasu.org/) and NAPPA core service and facility (http://nappaproteinarray.org/), which distribute plasmid cDNAs and NAPPA arrays at academic prices, respectively 28,38 .…”
Section: Introductionmentioning
confidence: 99%
“…We have widely published detailed protocols for producing NAPPA arrays, as well as published on recent improvements in the method 21,3537 . In addition, we have published a video tutorial for how to build NAPPA arrays (https://www.youtube.com/watch?v=Ur1fg9jQv04) 36 . Furthermore, researchers who do not have direct access to resources to build, print, screen, scan, or analyze their own arrays can make use of our central plasmid repository (https://dnasu.org/) and NAPPA core service and facility (http://nappaproteinarray.org/), which distribute plasmid cDNAs and NAPPA arrays at academic prices, respectively 28,38 .…”
Section: Introductionmentioning
confidence: 99%
“…Results of this study demonstrated that antibodies against one arabinomannan fragment were absent in the TB patients but present in the uninfected healthcare worker. In the second antigen microarray study, a nucleic acid programmable protein array (NAPPA) was created in which all 4000 Mtb genes were printed on an array surface and used to generate proteins using a cellfree expression system [30]. The NAPPA protein array was then probed with sera from latently infected controls and TB patients with and without HIV co-infection from the United States and South Africa.…”
Section: Potential Role Of Mucosal Humoral Responses In Contributing mentioning
confidence: 99%
“…Moreover, HCIVT showed a robust lot-to-lot reproducibility. In immune assays, the signals of many antigens were detected only in HCIVT-expressed arrays, mainly due to the reduction in the background signal and the increased levels of protein on the array [14,35]. The protein yields obtained through PURE system has then been matched to that obtained with this innovative cell free IVTT system.…”
Section: Fluorescence Analysismentioning
confidence: 99%